2007
DOI: 10.1016/j.ccr.2007.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of Different Human Breast Epithelial Cell Types Leads to Distinct Tumor Phenotypes

Abstract: We investigated the influence of normal cell phenotype on the neoplastic phenotype by comparing tumors derived from two different normal human mammary epithelial cell populations, one of which was isolated using a new culture medium. Transformation of these two cell populations with the same set of genetic elements yielded cells that formed tumor xenografts exhibiting major differences in histopathology, tumorigenicity, and metastatic behavior. While one cell type (HMECs) yielded squamous cell carcinomas, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
325
1
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 287 publications
(350 citation statements)
references
References 40 publications
22
325
1
2
Order By: Relevance
“…These results are consistent with other reports where Ras together with other oncogenes has been shown to induce the transformation of TERT-immortalized hMECs. 37,38 Notably, the mouse tumors formed by implanted EcdCRas overexpressing hMECs showed both epithelial and metaplastic components, consistent with stem/progenitor properties of TERT-immortalized hMECs. 7 Consistent with relaxation of cell cycle transit observed in EcdCRas overexpressing hMECs in vitro, the tumors arising from these cells had high proliferation index as measured by the proportion of Ki-67 positive cells, a known and commonly used marker of cell proliferation in tumors.…”
Section: Discussionmentioning
confidence: 87%
“…These results are consistent with other reports where Ras together with other oncogenes has been shown to induce the transformation of TERT-immortalized hMECs. 37,38 Notably, the mouse tumors formed by implanted EcdCRas overexpressing hMECs showed both epithelial and metaplastic components, consistent with stem/progenitor properties of TERT-immortalized hMECs. 7 Consistent with relaxation of cell cycle transit observed in EcdCRas overexpressing hMECs in vitro, the tumors arising from these cells had high proliferation index as measured by the proportion of Ki-67 positive cells, a known and commonly used marker of cell proliferation in tumors.…”
Section: Discussionmentioning
confidence: 87%
“…The HMLERs derived from adherent HMECs generated squamous cell carcinomas (Elenbaas et al, 2001), which represent o5% of naturally occurring breast cancers. The BPLERs derived from HMECs cultivated in specialized media called WIT generated malignant adenocarcinomas (Ince et al, 2007); however, both these models showed an absolute requirement for oncogenic Ras for transformation, while Ras mutations are found in o5% of naturally arising breast cancers. The Wnt-transformed HMECs generated medullary breast carcinomas (Ayyanan et al, 2006), which represent 2% of all breast tumors.…”
Section: Discussionmentioning
confidence: 99%
“…For example, overexpression of oncogenic Ras resulted in the transformation of HMLE cells, leading to the generation of squamous cell carcinoma (Elenbaas et al, 2001). In yet another study, HMECs grown in a specialized media called WIT and carrying SV40ER, hTERT and oncogenic Ras led to the generation of adenocarcinomas (Ince et al, 2007). However, both these latter models required supra-physiologic expression of oncogenic Ras, while mutations in the Ras oncogene are very rare in breast cancers (Rochlitz et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…When early passage human mammary epithelial cells were propagated in two alternative culture media, they yielded populations that exhibited distinct gene expression patterns and, upon transformation by these introduced genes, yielded tumorigenic cells that grew into two histopathologically distinct tumors-one a squamous cell carcinoma and the other an invasive ductal adenocarcinoma of the breast (6). These outcomes conform with a widely held preconception-that the differentiation program of the normal cell of origin is a strong determinant of the eventual behavior of tumor cells arising following transformation.…”
Section: Early Determinationmentioning
confidence: 99%